EXPLORING THE CONCEPT OF QASHASH IN T.M. HASBI ASH-SHIDDIEQY'S TAFSIR AL-QUR'ANUL MAJID AN-NUUR: A CRITICAL ANALYSIS - Yusmadi, Yusmadi; Maulida; Naufal , T. Ahmad; Ibrahim , Muhammad Syahrial Razali (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2025)
The concept of Qashash, which refers to the principle of equal retribution in Islamic law, plays a crucial role in upholding justice and fairness within society. T.M. Hasbi Ash-Shiddieqy's Tafsir al-Qur'anul Majid An-Nuur provides a unique perspective on Qashash, reflecting his attempt to contextualize this principle within the framework of Indonesian culture and society. This study critically examines Hasbi's interpretive methodology and the epistemological foundations he employed in understanding Qashash. Utilizing a library research approach, this paper explores the strengths and limitations of his interpretations and their relevance to contemporary Islamic thought. The findings reveal Hasbi's distinctive integration of rationality and contextuality, highlighting his efforts to bridge traditional Islamic teachings with modern realities. However, the study also identifies areas where his interpretations could further emphasize the universal dimensions of Qashash.